Using Project-Based-Learning in a mobile application development course—An experience report. (December 2015) - Francese, Rita; Gravino, Carmine; Risi, Michele; Scanniello, Giuseppe; Tortora, Genoveffa
Abstract: In this paper, we report the experience gained in a Mobile Application Development course. We involved students in Computer Science at the University of Salerno, who in teams had to conduct a project. The goal of this project was to design and develop applications (or simply app) for Android-based devices. The adopted teaching approach was based on Project-Based-Learning and enhanced collaboration and competition. Collaboration took place among members of the same team (intra-team), while competition among different teams of students (extra-team). To allow intra-team collaboration, students used GitHub as Computer-Supported-Collaborative-Learning tool. It provided support for implicit and explicit communication among members in each team and for distributed revision control and management of software artifacts (e.g., source code and requirements models). Developed apps underwent a final public competition prized by IT managers of national and international software companies. This is how we implemented extra-team competition. IT managers expressed a positive judgment on both students׳ competition and developed apps. Also, students provided very good feedback on used teaching approach and support GitHub provided.